COMPARING TYPES OF LESSONS AND APPROACHES TO LESSON PLANNING - Ubaydullaeva, Jamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the planning of the educational process implies the establishment of goals, tasks and educational results during a certain period and at the end. Planning will be successful if the following factors are taken into account. Ideas about lesson organization and comparison of approaches are shown.